The Role of Imports from the Newly-industrializing Countries in U.S. Production - Aw, Bee Yan; Roberts, Mark J. (The Review of Economics and Statistics, 1985)
This paper examines the relationship among U.S. imports from the NICs, imports from developed countries, capital, and labor in the production of goods for final demand. Import demand and substitution elasticities are estimated for the period 1960-80. U.S. imports from the NICs are found to be complements with both labor and imports from industrialized countries. This indicates that the substitution effect resulting from a reduction in the price of imports from the NICs would lead to a net increase in employment. Multilateral tariff cuts by the United States would increase the demand for NIC goods despite a reduction in their preferential tariff margins.